Use of Muscle Interpolation Flap as a Reconstructive Option in Soft Tissue Coverage of Limbs: A Novel Technique - Swain, Bharatendu; Sampreethi, Shalini (Indian Journal of Plastic Surgery, 2025)
In injuries of the hand or forearm with vascular compromise due to a single vessel supplying blood distally or difficulty in donor vessel access, a pedicled flap is preferred. Skin flaps like the groin flap are commonly used as an interpolation flap. Muscle flaps used as interpolation flaps have scarcely been reported in the literature. However, muscle has been a component of composite flaps used as interpolation flaps like the tongue flap. The authors have used pedicled, interpolated muscle flaps successfully in hand and heel reconstructions.Five patients with soft tissue loss due to trauma, in single vessel limbs or difficult donor vessel access, were taken up for interpolation muscle flap. Four of these patients underwent inferiorly based, upper rectus abdominis muscle flap delivered at the umbilicus, by endoscopy or the open method. One patient underwent a proximally based, medial head of the gastrocnemius, cross-leg flap. The muscle flaps were skin grafted. One month later, the flaps were delayed and divided shortly thereafter. The divided end of the muscle was dressed till it healed. All the patients were followed up for healing time, additional procedures, and long-term results.Five documented cases of reconstruction in single vessel limbs or difficult donor vessel access were reviewed. All five cases achieved good healing and intended reconstructive outcomes without any complications.An interpolation muscle flap is a safe and effective method for reconstructing limb defects. Both types of interpolation muscle flaps described are novel applications in reconstructive surgery.
Keywords: interpolation muscle flap; vascular compromise; hand reconstruction; heel reconstruction